Modeling and Simulation of Bragg Gratings on High Index Contrast and Surface Plasmonic Waveguides by Mode Matching Method - Mu, Jianwei (My University, 2007)
As the fundamental basic building blocks of photonic circuits, optical waveguide structures play important roles in modem telecommunication and sensing systems. Various structures ranging from the dielectric waveguide utilizing the total internal reflection (TIR) to the more advanced structures based on the surface plasmon polaritions (SPPs) are widely investigated and studied in industrial and research areas. With the fast development of fabrication technologies, more and more complicated structures are predicated to emerge as the requirement of highly integrated photonic circuits. Modeling and simulation methods, as efficient as well as excellent cost performance tools comparing to costly facilities and time-consuming fabrication procedures, are demanded to explore and design the devices and circuits before their finalization.
This thesis reports a series of techniques to model two dimensional waveguide structures, including the conventional planar and surface plasmon polariton waveguides. This thesis contains both the methods and their applications to model and investigate the mode and propagation characteristics including the guided waves and the radiative waves. The methods include mode solvers based on fmite difference method (FDM) and complex mode matching method (CMMM), furnished with perfect matching layer (PML) for both guided and radiation modes. Based on the developed techniques, solutions of design of Bragg gratings with deep corrugations are presented; also various surface plasmon polariton (SPPS) grating structures are investigated.
Keywords: Simulation; Bragg Gratings; High Index Contrast; Surface Plasmonic; Waveguides; Mode Matching